Daratumumab plus lenalidomide/dexamethasone in untreated multiple myeloma: analysis of key subgroups of the MAIA study - Moreau, Philippe; Facon, Thierry; Usmani, Saad Z.; Bahlis, Nizar; Raje, Noopur; Plesner, Torben; Orlowski, Robert Z.; Basu, Supratik; Nahi, Hareth; Hulin, Cyrille; Quach, Hang; Goldschmidt, Hartmut; et al. (Leukemia, 2025)
In the MAIA study (median follow-up, 56.2 months), daratumumab plus lenalidomide and dexamethasone (D-Rd) significantly improved progression-free survival (PFS) and overall survival versus lenalidomide and dexamethasone (Rd) alone in transplant-ineligible newly diagnosed multiple myeloma (NDMM). In this post hoc analysis of clinically important subgroups in MAIA (median follow-up, 64.5 months), transplant-ineligible patients with NDMM were randomized 1:1 to D-Rd or Rd. The primary endpoint was PFS; secondary endpoints included overall response rate (ORR) and measurable residual disease (MRD)-negativity rate (10-5). PFS favored D-Rd versus Rd in most subgroups, including patients aged ≥75 years (HR, 0.59; 95% CI, 0.44-0.79), frail patients (HR, 0.64; 95% CI, 0.48-0.85), patients with high-risk cytogenetics (HR, 0.59; 95% CI, 0.44-0.80), and patients with isolated gain(1q21) (HR, 0.36; 95% CI, 0.19-0.67). ORRs, MRD-negativity rates, and sustained (≥12 months) MRD-negativity rates were higher with D-Rd versus Rd across subgroups. In patients aged ≥75 years, rates of grade 3/4 and serious treatment-emergent adverse events (TEAEs) were similar for D-Rd and Rd, but discontinuation due to TEAEs was lower for D-Rd. Results support use of D-Rd for high-risk patients, supporting D-Rd as a standard of care for transplant-ineligible NDMM. This trial was registered at www.clinicaltrials.govas NCT02252172.